HIV‐associated neurocognitive disorder in HIV‐infected Koreans: the Korean NeuroAIDS Project. Issue 8 (24th February 2014) - Ku, NS; Lee, Y; Ahn, JY; Song, JE; Kim, MH; Kim, SB; Jeong, SJ; Hong, K‐W; Kim, E; Han, SH; Song, JY; Cheong, HJ; et al.
<x xml:space="preserve">Abstract</x> Objectives HIV‐associated neurocognitive disorder (HAND) is an independent predictor of early mortality and is associated with many difficulties in activities of daily living. We sought to determine the prevalence of and risk factors for HAND in HIV‐infected Koreans. In addition, we investigated the performance of screening tools and components of neuropsychological (NP) tests for diagnosing HAND. Methods HIV‐infected patients were enrolled consecutively from two different urban teaching hospitals in Seoul, South Korea between March 2012 and September 2012. Participants completed a detailed NP assessment of six cognitive domains commonly affected by HIV. The Frascati criteria were used for diagnosing HAND. Four key questions, the International HIV Dementia Scale (IHDS) and Montreal Cognitive Assessment (MoCA)‐K were also assessed as potential tools for screening for HAND. Results Among the 194 participants, the prevalence of HAND was 26.3%. Asymptomatic neurocognitive impairment and minor neurocognitive disorder accounted for 52.9 and 47.1% of the patients with HAND, respectively. In multivariate analysis, haemoglobin (Hb) level ≤ 13 g/dL (P = 0.046) and current use of a protease inhibitor‐based regimen (P = 0.031) were independent risk factors for HAND. The sensitivity and specificity of the IHDS were 72.6 and 60.8%, and those of MoCA‐K were 52.9 and 73.4%, respectively. The IHDS (P < 0.001) and MoCA‐K (P < 0.001) were both useful for screening for HAND. Among NP tests, the sensitivity and specificity of the Grooved Pegboard Test were 90.2 and 72.0%, and those of the Wisconsin Card Sorting Test were 61.2 and 84.4%, respectively. Conclusions HAND is a prevalent comorbidity in HIV‐infected Koreans. Active screening and diagnosis with effective tools, such as the IHDS, MoCA‐K and Grooved Pegboard Test, could be used to identify this important complication.